An intervention for fears and phobias in young people with autism spectrum disorders using flat screen computer-delivered virtual reality and cognitive behaviour therapy. (March 2019) - Maskey, Morag; McConachie, Helen; Rodgers, Jacqui; Grahame, Victoria; Maxwell, Jessica; Tavernor, Laura; Parr, Jeremy R.
Highlights: Anxiety is among the most common reasons for referral of children and adolescents with ASD to health services; many have situation specific anxiety, fear and phobias. A recent review of treatment for fear and phobias in autism found, with one exception, only small studies of behavioural and cognitive behaviour therapy (CBT). Adaptations to CBT have been advised by the National Institute for Health and Care Excellence (NICE) to increase the effectiveness of treatment for autistic people. Abstract: Background: Specific fears and phobias are common in young people with autism spectrum disorder (ASD) and can impact greatly on daily functioning. Traditional treatment methods, such as real-life or imaginal exposure, may not be suitable for this population without adaptation and alternative interventions are needed. In previous studies, we established that delivering graded exposure through computer generated scenes in a fully immersive virtual reality environment (the Blue Room) is an effective intervention for some young people with ASD and specific fears/phobias. In this study, we explored the same intervention delivered using flat screen, computer-delivered virtual reality graded exposure with cognitive behavioural therapy. Methods: Eight young people with ASD received one psychoeducation session followed by four 20 minute sessions of flat screen, computer–delivered virtual reality graded exposure with cognitive behaviour therapy (CBT) sessions with a psychologist. Follow up measures, including Target Behaviour change ratings, were taken at 6 weeks, 6 months and 12 months after intervention. Results: Four of the participants were classed as responders to the intervention and were able to function without the fear/phobia impacting their life. These improvements were maintained 12 months post-intervention. One participant was lost to follow-up and three participants were classed as non-responders to the intervention. Conclusions: Findings show that flat screen computer-delivered virtual reality with cognitive behaviour therapy can be an effective intervention for specific fears and phobias for some young people with ASD.